Penerapan Teknologi Tepat Guna dalam Pengolahan Sereh Wangi menjadi Minyak Atsiri melalui Metode Ekstraksi Hydrodistillation - Nur Ida Iriani; Tirta Yoga Yoga; Zuhdi Ma’sum; Agnes Quartina Pudjiastuti (Institut Pertanian Bogor, 2026)
This community service program was implemented in collaboration with the Panderman Forest Farmer Group (KTH Panderman) in Batu City, East Java, Indonesia. The program aimed to enhance the knowledge and technical skills of farmer group members in processing citronella grass into essential oil through the application of an innovative hydrodistillation process. The participants consisted of 20 members of KTH Panderman who had prior experience in the cultivation and conventional processing of citronella grass. The program employed a participatory approach involving problem identification, counseling, training, mentoring, and the application of technology in post-harvest handling and extraction processes. The implemented innovations included the selection of raw materials based on harvest age, the use of leaves as the primary extraction material, a wilting process prior to extraction, and improvements to the oil separation system. The hydrodistillation process was conducted using water as the extraction medium without the addition of organic solvents, at an operating temperature of approximately 95–100°C. The results demonstrated improvements in both production capacity and processing efficiency. Extraction time was reduced from 3 hours to 2 hours, raw material processing capacity increased from 20 kg to 30 kg per batch, and the volume of essential oil produced increased from an average of 40–45 mL to 80–100 mL per batch. These improvements were achieved through enhanced raw material handling practices and optimization of the oil separation process during extraction. Overall, the program successfully improved the technical capacity of farmer group members and increased the productivity of citronella essential oil production.